Stackelberg game based energy optimization for unmanned aerial vehicle assisted wireless-powered Internet of things - Xumin HUANG; Yang ZHANG; Rong YU; Li JIANG; Hui TIAN; Yuan WU (Tongxin xuebao)
The technology integrating unmanned aerial vehicles (UAV) with wireless power transfer is applied to provide energy supply for Internet of things devices.A Stackelberg game scheme was further proposed to tackle the problem on free and fair energy trading between a charging user and multiple UAV.The user played as a game leader and determined the rewards while each UAV played as a game follower, which competed for the rewards through the energy supply, and refered to the average channel gain during the wireless power transfer to determine the charging time for the user.The Stackelberg equilibrium solution was analyzed and derived by the backward induction method.Simulation results show that the proposed scheme can effectively reduce the economic cost for the user in the energy trading, thereby improving user satisfaction and achieving the user-side energy optimization.